Price Variability and Beef Market Integration in Java - Fajar Andriansyah; Asifa Asifa; Luluk Isnaini; Sahara Sahara (Faculty of Animal and Agricultural Science, Diponegoro University, 2025)
The high demand for beef for consumption activities that is not accompanied by the adequacy of domestic production causes instability in the beef market and has an impact on prices that tend to fluctuate. In response to this, the government implements various policies such as import fulfillment, self-sufficiency and the establishment of beef production centers, but this is also an obstacle in meeting the uneven demand for beef in each region. The purpose of this study is to find out the variability and changes in beef prices as well as how the asymmetry of beef prices at each level of the beef market on the island of Java. Data analysis uses the variance of quantitative statistical coefficients and econometric models of the ECM and Houck approaches. The results show that the variation in beef prices on the island of Java, namely in the provinces of Banten, West Java, Central Java and East Java, is at a low level of variation with significant fluctuating price changes. In addition, there is a price asymmetry relationship between the market level of wholesalers and traditional markets and vice versa in West Java, Central Java and East Java as well as from traditional markets to wholesalers in Banten. This identifies that there is no balance between each level of the beef market in Java, which is allegedly caused by various factors, including commodity characteristics, infrastructure, and local market dynamics. Therefore, better policies are needed to stabilize prices and improve the efficiency of beef distribution.